2003
DOI: 10.1128/jvi.77.7.4160-4168.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus RNA Replication Occurs on a Detergent-Resistant Membrane That Cofractionates with Caveolin-2

Abstract: The mechanism and machinery of hepatitis C virus (HCV) RNA replication are still poorly understood. In this study, we labeled de novo-synthesized viral RNA in situ with bromouridine triphosphate (BrUTP) in Huh7 cells expressing an HCV subgenomic replicon. By immunofluorescence staining using an anti-BrUTP antibody and confocal microscopy, we showed that the newly synthesized HCV RNA was localized to distinct speckle-like structures, which also contain all of the HCV nonstructural (NS) proteins. These speckles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
210
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 246 publications
(232 citation statements)
references
References 60 publications
19
210
3
Order By: Relevance
“…Previously, we have shown that HCV RNA replication occurs on speckle-like structures [29], which may be equivalent to the membranous web, as reported by Gosert et al [45]. The immunofluorescence staining study presented here showed that PTB in Huh-7 cells mainly existed in the nucleus, while PTB in the replicon cells localized in not only the nucleus but also distinct structures in the cytoplasm and colocalized with the newly synthesized HCV RNA (Figure 1).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Previously, we have shown that HCV RNA replication occurs on speckle-like structures [29], which may be equivalent to the membranous web, as reported by Gosert et al [45]. The immunofluorescence staining study presented here showed that PTB in Huh-7 cells mainly existed in the nucleus, while PTB in the replicon cells localized in not only the nucleus but also distinct structures in the cytoplasm and colocalized with the newly synthesized HCV RNA (Figure 1).…”
Section: Discussionsupporting
confidence: 85%
“…Significantly, PTB was detected in this membrane fraction in the replicon-containing cells, but not in Huh-7 cells. As shown previously, caveolin-2, a known DRM-resident protein was detected in the DRM fraction of both Huh-7 and replicon cells (29,31; see also Figure 4). These results indicated that PTB, together with the HCV NS proteins and hVAP-33, was present as large complexes in the DRM fraction.…”
Section: Ptb Localized In Membrane Fractions Of Replicon Cellssupporting
confidence: 82%
See 3 more Smart Citations